Zirconium(IV) Phosphonate–Phosphates as Efficient Ion-Exchange Materials - Silbernagel, Rita; Martin, Caroline H; Clearfield, Abraham (Inorganic chemistry, 2016)
Layered metal phosphonate–phosphate hybrid materials are known to be ion-exchange materials. Hybrids with zirconium metal centers were synthesized at varying phosphonate–phosphate ratios in order to explore the function and charge preference. The zirconium hybrid materials were found to have a range of applicable uses with preference for highly charged ions (3+) over lower charged ions (1+ and 2+). The addition of a large excess of phosphate altered the selectivity, and these materials were able to remove all ions from solution regardless of charge. In this paper, we describe newly synthesized compounds that are simple to prepare, reproducible, stable, and offer a variety of separation schemes.